2010
DOI: 10.1007/s11270-010-0483-0
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Impact of Exposure to Airborne Particulate Matter in Pearl River Delta, China

Abstract: To evaluate the potential public health impact of exposure to airborne particulate matter, concentrations of PM 10 and PM 2.5 were measured at 16 monitoring stations in Pearl River Delta. Epidemiological studies were collected, and meta-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…Economic losses caused by air pollution were estimated to be 292 billion RMB in 2006, accounting for 1.35% of the regional Gross Domestic Product (GDP) [26]. As a consequence, the increase in hazy days and deteriorating air quality, greatly impairing the health of the population and the visibility over the region, has drawn widespread attention from the Chinese government and the public [27][28][29][30]. However, there is still a lack of AOT-based estimations for PM concentrations in this area currently.…”
Section: Introductionmentioning
confidence: 99%
“…Economic losses caused by air pollution were estimated to be 292 billion RMB in 2006, accounting for 1.35% of the regional Gross Domestic Product (GDP) [26]. As a consequence, the increase in hazy days and deteriorating air quality, greatly impairing the health of the population and the visibility over the region, has drawn widespread attention from the Chinese government and the public [27][28][29][30]. However, there is still a lack of AOT-based estimations for PM concentrations in this area currently.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of these targeted pollutants should be therefore monitored continuously and extensively to evaluate the effectiveness of the imposed control measures. Finally, the availability of pollutant concentrations from the network also helps to evaluate the pollution impacts, in term of the criteria pollutants including PM 10 , O 3 and SO 2 , on health and crop loss within the PRD region (Xie et al, 2011;Huang et al, 2012). This paper accounts for the nation's first regional air quality monitoring network development such as measurement technology, and data management and dissemination and Quality Assurance/Quality Control (QA/QC) system, reviews the monitoring results and looks ahead the upcoming challenges and priorities in tackling regional air pollution in the south coast of China.…”
Section: Introductionmentioning
confidence: 99%
“…These particulate matters are a major cause of disease transformation from factory workers to their family members, which become the ultimate cause of disease magnification in the community. Public health impact exposure to PMs includes both acute (with short-term effects) and chronic (with long-term effects) effects on people (Xie et al 2011). Recent epidemiological studies have found associations between increases in air particulates and increased morbidity and mortality, especially among sensitive subpopulations such as children, elderly, and those with preexisting respiratory and cardiac diseases (U.S. Environmental Protection Agency 1996).…”
Section: Introductionmentioning
confidence: 99%